THE ANALYSIS OF BUYING MOTIVES IN PURCHASE DECISION OF VIRTUAL GOODS IN ONLINE GAME - Ajara, Rizky (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2017)
ABSTRACT: This study is aimed to analyze consumers’ buying motives to purchase virtual goods in online games. The sample technique used purposive sampling technique because respondents selected in accordance with characteristic that meet the criteria in the study. Structured interviews were used to analyze respondents’ buying motives in purchase decision of virtual goods in online games. The data were collected by interviewing the respondent one-to-one discussion session. The buying motives has divided into 2 variables: product buying motives and patronage buying motives The result shows 7 indicators strongly influence consumer to do the purchasing of virtual goods in online games study finally recommended to the game developer to usually focus on improve the model of virtual goods and for the future study hopefully can do some research with focus on 1 game online. Keywords: Buying Motives. Purchase Decision. Online Game.Virtual Goods.